Maternal depression and offspring mental health at age 5: MINA-Brazil cohort study - Alicia Matijasevich; Alexandre Faisal-Cury; Isabel Giacomini; Julia de Souza Rodrigues; Marcia C. Castro; Marly A. Cardoso (Universidade de São Paulo, 2024)
ABSTRACT OBJECTIVE: To identify longitudinal patterns of maternal depression between three months and five years after child's birth, to examine predictor variables for these trajectories, and to evaluate whether distinct depression trajectories predict offspring mental health problems at age 5 years. METHODS: We used data from the Maternal and Child Health and Nutrition in Acre (MINA-Brazil) study, a population-based birth cohort in the Western Brazilian Amazon. Maternal depressive symptoms were assessed with the Edinburgh Postnatal Depression Scale (EPDS) at 3 and 6-8 months, and 1 and 2 years after delivery. Mental health problems in 5-year-old children were evaluated with the Strengths and Difficulties Questionnaire (SDQ) reported by parents. Trajectories of maternal depression were calculated using a group-based modelling approach. RESULTS: We identified four trajectories of maternal depressive symptoms: "low" (67.1%), "increasing" (11.5%), "decreasing" (17.4%), and "high-chronic" (4.0%). Women in the "high/chronic" trajectory were the poorest, least educated, and oldest compared with women in the other trajectory groups. Also, they were more frequently multiparous and reported smoking and having attended fewer prenatal consultations during pregnancy. In the adjusted analyses, the odds ratio of any SDQ disorder was 3.23 (95%CI: 2.00-5.22) and 2.87 (95%CI: 1.09-7.57) times higher among children of mothers belonging to the "increasing" and "high-chronic" trajectory groups, respectively, compared with those of mothers in the "low" depressive symptoms group. These differences were not explained by maternal and child characteristics included in multivariate analyses. CONCLUSIONS: We identified poorer mental health outcomes for children of mothers assigned to the "chronic/severe" and "increasing" depressive symptoms trajectories. Prevention and treatment initiatives to avoid the adverse short, medium, and long-term effects of maternal depression on offspring development should focus on women belonging to these groups.